Effect of thermal treatment conditions on the solid-state synthesis of barium zirconate from barium carbonate and monoclinic zirconia. Issue 18 (15th September 2021) - Bach, Miriam; Schemmel, Thomas; Hubálková, Jana; Bühringer, Maleachi; Jansen, Helge; Aneziris, Christos G.
Abstract: In the present work the solid-state synthesis of phase-pure barium zirconate (BaZrO3 ) using barium carbonate and monoclinic zirconia as powder raw materials is investigated. Due to the high evaporation tendency of BaO, special attention is paid to the thermogravimetric behaviour of stoichiometric mixtures of BaCO3 and ZrO2, namely without sintering aids. DSC/TG measurements of the powder mixtures were conducted to assess the synthesis reaction using heating rates of 1, 3 and 10 K min −1 . In addition to the investigations of the thermogravimetric behaviour in dependence of different heating rates, the influence of synthesis temperature and ceramic carrier grains was examined on pressed specimens of 50 mm in diameter. Moreover, the influence of three different partial pressure relations resulting from the decarbonisation reaction and the assumed BaO evaporation was investigated. It was found that a synthesis temperature of 1200 °C and a heating rate of 1 K min −1 resulted in the least pronounced mass loss and mass loss rate, respectively. XRD analyses revealed phase-purity for specimens of assumed low BaO evaporation. Thus, optimum thermal treatment conditions were identified for the BaZrO3 synthesis that can be applied to the production of phase-pure material for e.g. the refractory industry.